1983
DOI: 10.1021/j100231a016
|View full text |Cite
|
Sign up to set email alerts
|

Study of nitrate radical by laser-induced fluorescence

Abstract: t-Bu),BzN(O)nitrobenzyl bromide, 100-11-8; p-nitrobenzyl duryl nitrodide, 84802-29-9; methyl iodide, 74-88-4; N-methyl-N-tris(tert-bu-ty1)phenyl nitroxide radical, 33721-34-5; N-methoxy-N-tris-(tert-buty1)phenyl anilino radical, 64191-72-6; benzyl bromide, electrochemical cell. CHZ(CBHJNO2,,BzN(O)H,The nitrate radical, NO3, was directly detected by the laser-induced fluorescence method. The band structure of the fluorescence excitation spectrum was consistent with that of the absorption spectrum. The fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 1 publication
2
49
0
Order By: Relevance
“…It showed that the symmetry of the split excited states that govern the transition probabilities for right and left circular polarization in the MCDA spectra are inverted for the CO 3 -compared to the NO 3 . Table 1 show a comparison of the vibrational modes for NO 3 and CO 3 -radicals in beryl as estimated in this work from the MCDA spectra, with those of free NO 3 radicals detected by Laser-induced fluorescence after decomposition of nitric acid vapor [10,11]. For the CO 3 -radical only values for a non-axial symmetry were found in the literature.…”
mentioning
confidence: 92%
“…It showed that the symmetry of the split excited states that govern the transition probabilities for right and left circular polarization in the MCDA spectra are inverted for the CO 3 -compared to the NO 3 . Table 1 show a comparison of the vibrational modes for NO 3 and CO 3 -radicals in beryl as estimated in this work from the MCDA spectra, with those of free NO 3 radicals detected by Laser-induced fluorescence after decomposition of nitric acid vapor [10,11]. For the CO 3 -radical only values for a non-axial symmetry were found in the literature.…”
mentioning
confidence: 92%
“…It has been the focus of a large body of spectroscopic work due to its complexity and difficulty in making state assignments. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Theoretically, numerous papers have appeared dealing with various aspects of the electronic structure and vibrational analysis [15][16][17][18][19][20][21] and we refer the reader to those papers for details. We note that theoretical work on vibrational assignments done by Stanton has used a model vibronic Hamiltonian, developed by Köppel−Domcke−Cederbaum, 22 with high-level ab initio input and some empirical scaling of the diabatic coupling to obtain good agreement with experiment.…”
mentioning
confidence: 99%
“…The peculiar features of the NO /O 3 and NO 2 /O 3 systems, deduced from the combination of our experimental and theoretical results, are illustrated in the energy profiles of Figures 9 and 10. Starting from NO , both the O 2 -and O-transfer reactions (10) and (11) …”
Section: Discussionmentioning
confidence: 99%
“…NO 3 . was produced in situ by reaction of NO 2 with O 3 , according to an established procedure, [10] and ionized by low-energy (40 eV) electron ionization (EI). The CAD spectrum, shown in Figure 3a, displays wide Gaussiantype peaks of m/z 46 (NO 2 ) and m/z 30 (NO ), consistent with the expected O-NO 2 connectivity.…”
Section: Introductionmentioning
confidence: 99%